Comment les chefs d'établissement scolaire peuvent-ils promouvoir l'innovation ? ou comment éviter de jouer l'efficacité contre elle-même ? - Vincent Lorius
Eadteachers are frequently presented as essential vehicles for the implementation of innovations. Yet the analysis of the functioning of the school institution shows that if the latter calls for change, rather it is a barrier to innovation. The reason is a pathology report to the standard of efficiency that induces compliance promotion more than the search for real improvements for students. In this paper, we propose some ideas for eadteacheers can overcome this difficulty. We indicate in particular how the normative plurality that characterizes the institutional environment can be used to return, for an innovation that concerns the effects it produces, personal judgment of the actors.